Changes in management actions after the Hospital Accreditation - Andréia Guerra Siman; Simone Graziele Silva Cunha; Maria José Menezes Brito (Universidade Federal do Ceará, 2016)
Objective: to understand the changes in the management actions after the Hospital Accreditation. Methods: a case study. The study included 12 managers of a hospital accredited with excellence. Data collection was carried out with interviews with semi-structured and subjected to content analysis. Results: about changes in management actions were recorded significantly three categories: Work organization with quality tools; management actions before and after the accreditation; and challenges faced by modifying the management actions. Conclusion: accreditation mobilized changes in management actions with quality instruments of adoption used to organize the work and accountability of those involved in the process. However, there were challenges to be overcome to achieve accreditation by managers.